Broad spectrum artificial light at night increases the conspicuousness of camouflaged prey. Issue 5 (25th March 2022) - McMahon, Oak; Smyth, Tim; Davies, Thomas W.
Abstract: The growing global prevalence of energy efficient broad spectrum lighting threatens to disrupt an array of visually guided ecological processes. Broad spectrum lighting likely better enables the discrimination of colour, yet it is potential to increase the conspicuousness of camouflaged prey at night remains little explored. Using a well‐established visual model, we quantified the impacts of four spectrally distinct narrow and broad spectrum lighting technologies on the conspicuousness of three different polymorphic colour variations of intertidal littorinid snail, as viewed by three model predators. Modern broad spectrum lighting technologies increased the conspicuousness of prey compared to 20th‐century narrow spectrum lighting. This effect was most prominent in the yellow colour morphs due to greater contrast with their natural fucoid seaweed background. Synthesis and applications . Our results provide evidence that the global transition to broad spectrum lighting will decrease the efficacy of camouflage at night in nature, potentially altering selective predation, population dynamics and the genetic structure of polymorphic populations. These findings highlight the need for further consideration in environmental management and planning, to ensure habitats are protected from unnecessary exposure to artificial light. Abstract : Our results provide evidence that the global transition to broad spectrum lighting will decrease the efficacy of camouflage at night in nature, potentially altering selective predation, population dynamics and the genetic structure of polymorphic populations. These findings highlight the need for further consideration in environmental management and planning, to ensure habitats are protected from unnecessary exposure to artificial light.